Organic Syntheses 2014
DOI: 10.1002/0471264229.os090.26
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Cyanate‐To‐Isocyanate Rearrangement: Preparation of tert ‐Butyl 3,7‐Dimethylocta‐1,6‐dien‐3‐ylcarbamate

Abstract: Geraniol Dichloromethane Trichloroacetyl isocyanate Trichloroacetyl carbamate Methanol Potassium carbonate ( E )‐3,7‐Dimethylocta‐2,6‐dien‐1‐ylcarbamate Triphenylphosphine Triethylamine Carbon tetrabromide t ‐Butyl 3,7‐dimethylocta‐1,6‐dien‐3‐ylcarbamate 3‐Isocyanato‐3,7‐dimethylocta‐1,6‐diene Tetrahydrofuran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Hydrogen-bonding and/or π-stacking interactions between the benzamide residue of substrate 13 and the activated form of 6-methylsalicylic acid may be responsible. Treatment of compound 14 with 2,2,2-trichloroacetyl isocyanate in dichloromethane led, after treatment with methanol and silica gel then aqueous workup, to carbamate 15 (88%).…”
mentioning
confidence: 99%
“…Hydrogen-bonding and/or π-stacking interactions between the benzamide residue of substrate 13 and the activated form of 6-methylsalicylic acid may be responsible. Treatment of compound 14 with 2,2,2-trichloroacetyl isocyanate in dichloromethane led, after treatment with methanol and silica gel then aqueous workup, to carbamate 15 (88%).…”
mentioning
confidence: 99%
“…Isocyanates 19 reacted further in an MoO 2 Cl 2 (DMF) 2 ‐catalyzed reaction with t BuOH to give carbamates 20 . The use of t BuOLi instead of the Mo catalyst in the second step of the synthesis of carbamate 20a and/or PPh 3 , CBr 4 , and Et 3 N, for the generation of cyanate 18a resulted in almost the same chirality transfer, but somewhat lower yields. Carbamates 19 were hydrolyzed under basic conditions to give the free amines in excellent yields, with very good chirality transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Ichikawa et al reported the synthesis of tert ‐butyl 3,7‐dimethylocta‐1,6‐dien‐3‐ylcarbamate ( 9 ) from the primary carbamate 7 , using triphenylphosphine, carbon tetrabromide, and triethylamine as dehydration system below room temperature (Scheme ) . Compound 8 is stable enough to be washed with a saturated aqueous NaHCO 3 solution or purified through a short column of silica gel.…”
Section: From Simple Allylic Alcohols To More Complex Substratesmentioning
confidence: 99%